Heathen: Religion and Race in American History - Gin Lum, Kathryn ca. 20./21. Jh. (Harvard University Press, 2022)
American ideas about race owe much to the notion of an undifferentiated "heathen world" held together by its need of assistance. This religious notion shaped American racial governance and undergirds American exceptionalism, even as purported heathens have drawn on their characterization as such to push back against this national myth.